The RELATIONSHIP BETWEEN LEVEL OF KNOWLEDGE AND SELF-MANAGEMENT OF TYPE 2 DIABETES MELLITUS PATIENTS AT BANDUNG GENERAL HOSPITAL MEDAN 2022 - CHANDRES VALERIUS MANALU (Jurnal Penelitian Keperawatan Medik, 2023)
ABSTRACT Chronic hyperglycemia and various metabolic disorders caused by unbalanced hormones can then cause chronic complications that occur in blood vessels, damage to the eyes, impaired kidney performance, and damage to the basement membrane (Phitri & Widiyaningsih, 2013). This type of research uses a quantitative type. This type of quantitative research is analytic through a cross-sectional approach to determine a relationship between one variable and another. The results of the research from 40 respondents answered that the respondents had a good level of knowledge, namely 27 respondents (67.5%) and the least, namely the level of knowledge was not good, 6 respondents (15.0%), good self-management, namely 20 respondents (50.0%) and the least is self-management, there are 6 respondents (15.0%). Based on the results of the analysis using the chi-square test, a p value <0.05 (p=0.000) was obtained with the result there was a significant relationship between the level of knowledge and self-management in patients with diabetes mellitus type two. Keywords: Level of Knowledge, Self-management, Type two Diabetes Mellitus